Why Consumers Commit Voluntarily to Collaborative Innovation with Firms by Using Social Media?: Case of Japanese consumers - Hiroki Idota; Joji Nakaya; Masatsugu Tsuji (International Telecommunications Society (ITS), 2019)
It is necessary to grasp and utilize consumer's needs for firms to improve existing products and developing new products. Especially, collaboration with consumers for product innovation is indispensable. On the other hand, social media has been spreading all over the world. Network communities formed by social media are one of key factors of innovation achieved by collaborating with consumer innovators, which is referred to as consumer collaborative innovation. This paper studies how Japanese firms achieve consumer collaborative innovation based on authors' questionnaire survey data in Japan. In particular, the types of users and the strength of ties between firms and consumers and types of consumer innovators are focused on. In addition, consumers' motivation of collaboration such as the intrinsic and extrinsic motivations of lead users and collaborative innovators are elucidated. This paper finds the role of lead users and pecuniary rewards which are more important than other motivations. Based on results obtained, some measures to promote consumer collaborative innovation in Japan are proposed.
Keywords: 330; Consumer collaborative innovation; social media; network community; lead user; motivation; monetary rewards